Acute stressors and clinical characteristics differentiate death by suicide, accident, or natural causes among illicit and prescription opiate users - Athey, Alison J.; Beale, Eleanor E.; Overholser, James C.; Stockmeier, Craig A.; Bagge, Courtney L. (Drug and Alcohol Dependence, 2020)
•Compared opioid users who died by natural cases, accidents, and suicide.•Substance use and suicide risk were evaluated using psychological autopsy methods.•Suicide completer sample significant for depression and previous suicide attempt.•Accidental overdose sample significant for a chronic pattern of severe drug abuse. Opiate misuse has reached epidemic levels. Prevention efforts depend on distinguishing opiate users from abusers. The current study compared opioid users who died by natural cases, accidents, and suicide using psychological autopsy methods. Groups were compared on substance use characteristics, treatment history, experiences of negative life events, and circumstances at the time of death. Substance use and suicide risk were evaluated using psychological autopsy methods in 63 decedents with positive toxicology for opiates at death divided into three groups: adults dying by suicide (n = 19), accident (n = 19), and natural causes (n = 25). Groups were compared on several dependent measures, using chi-square analyses to examine categorical variables and one-way analyses of variance (ANOVA) to examine continuous variables. Individuals who died by suicide were similar in many ways to adults who died by an accidental overdose. However, suicide completers were more likely to have struggled with severe depression, and previously attempted suicide, whereas the accidental overdose sample was more likely to display a chronic pattern of severe drug abuse. The current study helps to distinguish between opiate users who are at risk for death by an accidental or intentional overdose. In the ongoing opiate crisis, clinicians must understand the risk of overdose and the nuances of accidental behaviors compared to purposeful ones. Signs of suicidal planning, relevant psychopathology, and ongoing life stress may be useful points of intervention for stopping the increasing number of deaths among opiate users.